Menumbuhkan Kesadaran Lingkungan Melalui Pendampingan Pengelolaan Sampah Terhadap Siswa Kelas 5 Mi Islamiyah Balong Gerih - Janna 'Alawiyah; Sofi Wiranta Paduri; Muhammad Imam Solih; Waladun Nur Ilham; Joko Purnomo (Jurnal Abdikarya Pembangunan, 2023)
Abstract: This research aims to raise environmental awareness through waste management for 5th-grade students of MI Islamiyah Balong. This research used direct teaching methods on students' trash disposal behavior. The research sample consisted of 34 grade 5 students who were randomly selected. Data were analyzed using quantitative descriptive analysis. The study results show that sound waste management can foster students' environmental awareness, especially in disposing of waste in its place. There was a significant increase in student behavior after receiving direct teaching and supervision in disposing of destruction in its place.